PENINGKATAN HASIL BELAJAR IPS DENGAN MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK DI KELASIV SEKOLAH DASAR - winda, eka permata; Nasrul, Nasrul; Eliyasni, Rifda (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
AbstractThe purposeof this study was to describe the improvement of student learning outcomes in teaching Citizenship Education (Civics) by using the talking stick in  class IV SDN 04 Koto Ranah .By fifth grade students study subjects totaling 14 people..Research that has been conducted shows an increase inboththe learning process and assessment of student learning outcomes. Results of research conducted in two cycles shows that the results of the assessment in terms ofplanning (RPP) in the first cycle is 73% rise in the second cycle to be 93%.Assessment results in terms oft he implementation aspects of the teacher in the first cycle increased 72% to 92,5%, while theresults of the assessment in terms ofthe implementation aspects of the students in the first cycle was a 70% increase in cycle II increased to 95%. Learning outcomes in the first cycle is rising 72% to 86% in the second cycle. So talking stickmodel can talking stick outcomes Civics.Keyword : student’s achivement in Social subject, talking stick pproach